Psychiatry : breaking the ICE : introductions, common tasks, emergencies for trainees - Stringer, Sarah; Hurn, Juliet; Husain, Mujtaba (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2015)
Psychiatry: Breaking the ICE contains everything psychiatry trainees need in order feel confident and competent in general adult inpatient and community placements.-A practical and reassuring guide to life as a psychiatrist, structured around the tasks expected both in day-to-day practice and in out-of-hours work -Key themes running throughout the book include ethical and legal issues, risk assessment and management, patient experience and safe prescribing -The authors are closely involved in the training, mentoring and supervision of core trainees, and know the real-world challenges faced by junior psychiatrists.
Introduction. Welcome / Sarah Stringer -- Mental health services overview / Christina Barras, Rory Conn, Laurine Hanna, Abigail G Crutchlow, Juliet Hurn -- Your team / Christina Barras, Rory Conn, Laurine Hanna, Abigail G Crutchlow -- Your role / Christina Barras, Rory Conn, Laurine Hanna, Abigail G Crutchlow -- Getting started / Mujtaba Husain, Christina Barras, Rory Conn, Laurine Hanna -- Safety and verbal de-escalation / Sarah Stringer -- Boundaries, time management and burnout / Sarah Stringer, Christina Barras, Rory Conn, Laurine Hanna -- Psychiatric assessment / Sarah Stringer, Mujtaba Husain, Penelope Brown, Sean Cross -- MANAGEMENT: GENERAL PRINCIPLES / Sarah Stringer -- Physical healthcare / Katherine Beck, Stephanie Young, Juliet Hurn -- MEDICATIONS / Noreen Jakeman, Sarah Stringer -- Psychological interventions / Jane Bunclark, Natasha Liu-Thwaites, Cheryl Kipping, Juliet Hurn, Sarah Stringer -- Social interventions / Christina Barras, Rory Conn, Laurine Hanna, Abigail G Crutchlow, Juliet Hurn, Rachel Thomasson, Anna M Burnside -- Handovers / Rachel Thomasson -- MENTAL HEALTH LEGISLATION / Penelope Brown, Peter Hindley, Anna M Burnside -- Compliments, complaints and serious incidents / Anna M Burnside, Sarah Stringer -- Training in psychiatry / Mujtaba Husain, Juliet Hurn, Rachel Thomasson, Christina Barras, Rory Conn, Laurine Hanna, Sarah Stringer -- Common tasks. COMMUNITY MENTAL HEALTH TEAM (CMHT): Outpatient clinics / Christina Barras, Rory Conn, Laurine Hanna -- CARE PROGRAMME APPROACH (CPA) MEETINGS / Abigail G Crutchlow, Christina Barras, Rory Conn, Laurine Hanna -- HOME VISITS / Laurine Hanna -- Depression / Rory Conn, Rachel Thomasson -- Generalised anxiety disorder (GAD) / Laurine Hanna -- First episode psychosis (FEP) / Christina Barras, Juliet Hurn -- Psychosis : longer term / Stephanie Young -- Bipolar affective disorder (BPAD) / Rory Conn, Juliet Hurn -- Emotionally unstable personality disorder (EUPD) / Jane Bunclark, Juliet Hurn -- Non-engagement or disengagement / Rory Conn -- Patients with forensic histories / Penelope Brown -- Pregnancy / Anna M Burnside, Noreen Jakeman -- Older adults / Vivienne Mak, Sean Lubbe -- Trauma and asylum / Laurine Hanna, Juliet Hurn -- Driving / Christina Barras -- Discharge / Laurine Hanna -- WARD: From admission to discharge / Katherine Beck, Abigail G Crutchlow -- Ward rounds / Katherine Beck -- Common side effect management / Katherine Beck, Noreen Jakeman, Sarah Stringer -- Clozapine / Stephanie Young, Noreen Jakeman -- Self-discharge and section 5(2) / Abigail G Crutchlow -- Seclusion reviews / Katherine Beck -- Alcohol misuse / Lisa Conlan, Isabel McMullen, Cheryl Kipping -- Illicit drugs / Isabel McMullen, Lisa Conlan, Cheryl Kipping -- Pregnant patients / Anna M Burnside -- Inpatients with forensic histories / Penelope Brown -- People with learning disabilities (LD) / Rory Sheehan -- Emotionally unstable personality disorder (EUPD) / Jane Bunclark, Juliet Hurn -- Older adults / Vivienne Mak, Sean Lubbe -- ELECTROCONVULSIVE THERAPY (ECT) / Sean Lubbe, Vivienne Mak -- SECTION 136 ASSESSMENTS / Anna M Burnside -- Tribunals / Sarah Stringer -- ON-CALL: Your first on-call shift / Rachel Thomasson, Sean Cross, Anna M Burnside -- Self-harm / Rachel Thomasson, Jane Bunclark, Sean Cross, Rory Conn, Christina Barras -- Self-harm in young people / Peter Hindley, Matthew Fernando -- First episode psychosis (FEP) / Rachel Thomasson -- Mania / Rachel Thomasson -- Delirium / Vivienne Mak, Sean Lubbe, Sean Cross -- Obsessive compulsive disorder (OCD) / Natasha Liu-Thwaites, Rachel Thomasson -- Panic attacks / Natasha Liu-Thwaites -- Drug-seeking / Isabel McMullen, Lisa Conlan -- Learning disability (LD) and behavioural change / Rory Sheehan --'Social' presentations / Sean Cross, Rachel Thomasson -- Medically unexplained symptoms / John Moriarty -- Emergencies. COMMUNITY MENTAL HEALTH TEAM (CMHT): Acute relapse / Laurine Hanna -- Adult safeguarding / Rory Conn, Vivienne Mak, Sean Lubbe -- WARD: Child protection concerns / Peter Hindley, Juliet Hurn, Sarah Stringer -- Medical emergencies / Katherine Beck, Abigail Steenstra -- OPIATE OVERDOSE / Isabel McMullen, Lisa Conlan -- Stiff, feverish patients / Anna M Burnside -- Catatonia / Anna M Burnside -- Lithium toxicity / Noreen Jakeman, Katherine Beck -- Alleged sexual assault / Anna M Burnside, Sarah Stringer, Penelope Brown -- Self-harm on the ward / Jane Bunclark, Abigail Steenstra -- Hanging / Anna M Burnside -- Death / Katherine Beck -- ON-CALL: Aggression / Abigail G Crutchlow, Christina Barras, Noreen Jakeman, Sean Lubbe, Vivienne Mak, Rachel Thomasson, Abigail Steenstra -- Challenging behaviour in children / Peter Hindley, Matthew Fernando -- Refusal of urgent treatment / Vivienne Mak, Sean Cross, Sean Lubbe, Rachel Thomasson -- Delirium tremens / Rachel Thomasson, Isabel McMullen, Lisa Conlan -- Puerperal psychosis / Anna M Burnside -- Eating disorders / Christina Barras, Sean Cross -- Threats of violence / Penelope Brown, Rachel Thomasson -- Appendices. Investigations/Monitoring -- Medications -- Alcohol and drugs -- Cognitive testing -- Mental health legislation -- Useful contacts.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Psychiatry -- Handbooks, manuals, etc; Positive psychology -- Handbooks, manuals, etc; Medical; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Positive psychology; Psychiatry; Physician's Role; Psychiatry; Physician-Patient Relations; Electronic books; Handbooks and manuals; Handbooks